2023
DOI: 10.3390/polym15112415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructure of Rice Husk Ash–Rubber–Fiber Concrete under Hygrothermal Environment

Abstract: In order to study the mechanical properties of rice husk ash–rubber–fiber concrete (RRFC) under hygrothermal environment, the optimal group was selected by orthogonal test. The mass loss, relative dynamic elastic modulus analysis, strength analysis, degradation degree analysis after cyclic loading and internal microstructure analysis of the optimal group of RRFC samples after dry–wet cycles under different environments and temperatures were compared and analyzed. The results show that the large specific surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The issue of using ash from these wastes in cement concrete technology and its effectiveness has been quite well studied, which is confirmed by various studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For example, in Salas Montoya et al (2023) [9] study, "the application of rice husk ash as a substitution of a part of the Portland cement" provided a fairly significant rise in strength properties, namely over 20% compared to the reference prototype.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The issue of using ash from these wastes in cement concrete technology and its effectiveness has been quite well studied, which is confirmed by various studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For example, in Salas Montoya et al (2023) [9] study, "the application of rice husk ash as a substitution of a part of the Portland cement" provided a fairly significant rise in strength properties, namely over 20% compared to the reference prototype.…”
Section: Introductionmentioning
confidence: 86%
“…In Rani & Jaya Krishna (2022) [15] study, the use of rice straw ash in an amount of 10% also improved "the compressive strength by 23.21% and tensile strength by 28.25% compared to the control composition". Studies [16][17][18][19][20] have confirmed the positive impact of rice husk and straw ash on the quality characteristics of composites in concrete technology.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations